Dorsolateral Prefrontal γ-Aminobutyric Acid in Men Predicts Individual Differences in Rash Impulsivity - Frederic Boy (Biological Psychiatry, 2011)
Background: Impulsivity is a multifaceted personality construct associated with numerous psychiatric disorders. Recent research has characterized four facets of impulsivity: “urgency” (the tendency to act rashly especially in the context of distress or cravings); “lack of premeditation” (not envisaging the consequences of actions); “lack of perseverance” (not staying focused on a task); and “sensation seeking” (engaging in exciting activities). Urgency is particularly associated with clinical populations and problematic disinhibited behavior.Methods: We used magnetic resonance spectroscopy to measure concentration of the inhibitory neurotransmitter -aminobutyric acid (GABA) in the dorsolateral prefrontal cortex (DLPFC) in two cohorts of 12 and 13 participants.Results: WefindthatvariationintraiturgencyinhealthymencorrelateswithGABAconcentrationintheDLPFC.Theresultwasreplicated in an independent cohort. More GABA predicted lower urgency scores, consistent with a role in self-control for GABA-mediated inhibitory mechanisms in DLPFC.Conclusions: These findings help account for individual differences in self-control and thus clarify the relationship between GABA and a wide range of psychiatric disorders associated with impaired self-control.